The making of a comprehensive transnational discourse community - Dieter Plehwe (Transnational Communities: Shaping Global Economic Governance, 2010)
The critique of state-centered approaches to international relations and international political economy has resulted in a rapidly growing literature focusing on a variety of “private authorities” in international relations (Cutler et al. 1999). In this literature, arrays of transnational communities are prominent subjects of analysis. Epistemic communities promoting new environmental standards, discourse communities pushing for new public management across borders, and advocacy coalitions shaming the perpetrators of human rights abuses, for example, have been observed and conceptualized in order to shed light on the extent to which dispersed actors from diverse locations can build and maintain crucial links, and develop social identities across borders. In turn, these have been found important for setting political agendas, acquiring a voice in policy implementation processes, policing compliance, and spreading ideologies more generally (Haas 1992a; Keck and Sikkink 1998; Bislev et al. 2002; Djelic 2006). At the same time, it is becoming clear that many of these transnational communities recruit their members among private as well as public constituencies. A study of these communities thus also needs specifically to address the linkages between civil society, business, and the public sphere. Transnational community research has also contributed to the rise of social constructivist approaches in international relations (Risse 2007). However, given the increasing attention paid to knowledge, ideas, and discourse, it is surprising how little international relations scholarship in general, and transnational community research in particular, have had to say so far about the global rise of neoliberal discourse.
Keywords: 300